Periodic, Rogue and Lump Soliton Solutions in Fiber Bragg Gratings for the Coupled Form of the Nonlinear (2+1)-Dimensional Kundu-Mukherjee-Naskar Equation - Abdumalik A. Altwaty; Amnnah Mohammed Ahmed Nasr; Ngla Farag Mahmoud-Meriki; Suhaylah Mahmoud Ali (African Journal of Advanced Pure and Applied Sciences, 2023)
In this article, the coupled version of the nonlinear (2+1)-dimensional Kundu-Mukherjee-Naskar equation in fiber bragg gratings was examined. To support the new optical solutions of the coupled form of the nonlinear (2+1)-dimensional Kundu-Mukherjee-Naskar equation in Fiber Bragg Gratings (FBGs), three well-known techniques were used: Periodic Cross-Kink wave, Rogue wave, and Lump interaction with kink and rogue waves. A novel type of traveling wave solution with interaction phenomena was produced by applying the proper functions of the solutions. Two and three-dimensional visualizations were used to depict the dynamics of the created solutions, demonstrating the dependability and effectiveness of the offered methods.